Important research outcomes for treatment studies of perinatal depression: systematic overview and development of a core outcome set. (20th June 2021) - Hellberg, C; Österberg, M; Jonsson, AK; Fundell, S; Trönnberg, F; Jonsson, M; Skalkidou, A
Abstract : Objective: To develop a Core Outcome Set (COS) for treatment of perinatal depression. Design: Systematic overview of outcomes reported in the literature and consensus development study. Setting: International. Population: Two hundred and twenty‐two participants, mainly patients, healthcare professionals and researchers, representing 13 countries. Methods: A systematic overview of outcomes reported in recently published research, a two‐round Delphi survey and a consensus meeting at which the final COS was decided using modified nominal group technique. Main results: In the literature search, 1772 abstracts were identified and evaluated, and 165 studies were finally included in the review. In all, 106 outcomes were identified and included in the Delphi survey. In all, 222 participants registered for the first round of the Delphi survey and 151 (68%) responded. In the second round, 123 (55%) participants responded. Thirteen participants attended the consensus meeting, where the following nine outcomes were agreed upon for inclusion in the final COS: self‐assessed symptoms of depression, diagnosis of depression by a clinician, parent to infant bonding, self‐assessed symptoms of anxiety, quality of life, satisfaction with intervention, suicidal thoughts, attempted or committed suicide, thoughts of harming the baby, and adverse events. Conclusions: The relevant stakeholders prioritised outcomes and reached consensus on a COS comprising nine outcomes. We expect that this COS will contribute to the consistency and uniformity of outcome selection and reporting in future clinical trials involving treatment of perinatal depression. Tweetable abstract: Development of a core outcome set regarding treatment for perinatal depression by @SBU_en. Tweetable abstract: Development of a core outcome set regarding treatment for perinatal depression by @SBU_en.